(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Isotonic solutions play a crucial role in pharmaceutical sciences, medical applications, and biological systems. This thesis examines the fundamental concepts of isotonic solutions, explores various methods for calculating isotonic concentrations, and discusses their practical applications. The osmotic pressure relationship between solutions and biological fluids determines the isotonic nature of pharmaceutical preparations.